Brand faithfulness and economic crisis. Brand and quality are important but price counts for more - Viviani, Debora (Italian Sociological Review, 2012)
This essay aims to analyze the relationship between brand faithfulness and the economic crisis, assessing whether there have been changes in the way people follow brands caused by the difficulties consumers find themselves faced with today. More specifically, it will attempt to answer the following questions: over the threeyear period 2009-2011, - have brands maintained their importance as a factor when purchasing consumer goods? - have consumers stayed faithful to the brands they always purchased before? - have the consumers stayed faithful to the brands with regard to the various retail sectors? These questions take their place within a much broader setting which we will analyze in order to determine whether brand faithfulness is weaker now than before. Our reflections will then focus on the main point of this essay. After analyzing which factors have the greatest influence on the choice of products – with the aim of determining the level of importance of the role brand plays – we will take a closer look at brand faithfulness in the consumers interviewed. Our aim in doing so is to determine whether the individuals interviewed are change-oriented or prefer not to change their choices of products and brands. This will allow us to understand whether brand plays a crucial role in consumption dynamics, pushing consumers towards change, or whether, on the contrary, habit, being sure of what one is buying, is what really counts.